Preparation and application of organic ligand based on metal chain support and heavy atom effect assisting metal
By preparing Cd-MOF materials, ligands react with metal ions to form a frame structure with metal chain brackets, the problems of harsh preparation conditions and insufficient performance in the prior art are solved, and a multi-color adjustable long continuous luminescence effect is achieved, which is suitable for applications such as anti-counterfeiting and information encryption.
Patent Information
- Application Number
- CN202411804227.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing commercially used long-lasting luminescent materials are mainly rare metal inorganic compounds, which have problems such as harsh preparation conditions, high cost and environmental pollution. The LPL performance of organic materials has not yet reached the level of inorganic materials and is difficult to widely use.
Cd-MOF was prepared by reacting ligand H2L with CdCl2·2.5H2O, using metal chain scaffolds and heavy atomic effects, an enhanced blue photoluminescence and a phosphorescence lifetime of 124ms were achieved, and lasted for 3 seconds at room temperature and could be from blue to green to yellow at lower temperatures.
It realizes the adjustable LPL performance of Cd-MOF materials, and can display long and continuous luminescence in multiple colors under different conditions, which is suitable for fields such as anti-counterfeiting and information encryption.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure HDA0005178786540000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal-organic framework long-lasting luminescent materials, and in particular to an organic ligand H2L and Cd 2+ Research on the preparation, properties and applications of self-assembled complexes. Background Art
[0002] Long persistent luminescence (LPL) means that the light can continue to be emitted for a long time after the excitation source is removed. In the past few decades, LPL materials have attracted much attention due to their potential applications in many commercial fields such as emergency lighting, interior decoration, traffic signs and displays, as well as their potential uses in optical recording devices, chemical sensors, biological imaging and security systems. At present, commercial LPL materials are mainly rare metal inorganic compounds. However, such materials have problems such as harsh preparation conditions, high cost and serious environmental pollution. In contrast, organic LPL materials have been widely studied in recent years. They have significant advantages such as easy design, low cost, good biocompatibility and low toxicity. However, it cannot be ignored that the LPL performance of organic materials is still inferior to that of inorganic materials, and there is still a certain gap from practical widespread application. In view of this, it is imperative to develop new LPL materials that are stable, cost-effective and energy-saving.
[0003] Organic phosphors, as guests, are physically or chemically doped into various hosts, such as metal organic frameworks (MOFs), macrocyclic cavities, steroidal compounds, and polymers, which can bring about room temperature phosphorescence (RTP) for carefully designed host-guest interactions. Among them, luminescence metal organic frameworks (LMOFs) have recently attracted widespread attention in basic research and industrial fields due to the combination of inorganic units and organic linkers. They have broad application prospects in display, drug delivery, and energy storage and conversion. On the one hand, coordination interactions can usually enhance the rigidity of molecular conformation, restrict the movement or vibration of molecules, and further reduce the non-radiative loss of triplet excitons, promoting phosphorescence emission. On the other hand, organic molecules containing heteroatoms such as N and O are ideal candidates for phosphorescent ligands, and those with d 10 The configured metal ions can increase the spin-orbit coupling of the system through the heavy atom effect and improve the intersystem crossing efficiency from singlet to triplet. Nevertheless, reports on MOFs with various conveniently tunable LPL colors are still very limited. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing Cd-MOF and its application, wherein the coordination compound is obtained by reacting the ligand H2L with CdCl2·2.5H2O to obtain the coordination compound Cd-MOF. Due to the scaffold and heavy atom effect of the metal chain in the skeleton, it exhibits enhanced blue photoluminescence and a phosphorescence lifetime of 124ms with the ligand under ambient conditions. It is worth noting that Cd-MOF exhibits interesting excitation, time and temperature dependent LPL, which lasts for 3s at room temperature, and can change from blue to green to yellow at lower temperatures. In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0005] A coordination compound Cd-MOF, characterized in that its molecular formula is: C7H5CdNO5, belongs to the monoclinic system, and has a space group of P21 / n.
[0006] The coordination compound Cd-MOF is prepared from the ligand H2L and CdCl2·2.5H2O. Specifically, the preparation method of the coordination compound Cd-MOF is as follows:
[0007] S1. Mix the ligand H2L and CdCl2·2.5H2O in a molar ratio of 1:1-2 and put them into a 25ml polytetrafluoroethylene-lined stainless steel container, add DMF, water and ethanol in a volume ratio of 1:1:1-1:2:2 into a 25ml polytetrafluoroethylene-lined stainless steel container, and shake gently to mix evenly; the usage ratio of DMF and ligand H2L is 1ml:0.01-0.02mmol.
[0008] S2. Place a sealed 25 ml polytetrafluoroethylene-lined stainless steel container in an oven, set the program, heat for 1 to 2 hours, raise the temperature from room temperature to 90 to 110 ° C, maintain this temperature for 40 to 60 hours, and then cool down after 8 to 13 hours;
[0009] S3. Collect the colorless block crystals by filtration.
[0010] Furthermore, in step S1, the molar ratio of the ligand H2L and CdCl2·2.5H2O is 1:1.
[0011] Furthermore, the volume ratio of DMF, water and ethanol in step S1 is 1 ml: 1 ml: 1 ml.
[0012] Furthermore, in step S1, the usage ratio of DMF to ligand H2L is 1 ml:0.1 mmol.
[0013] Furthermore, in step S2, the oven program is set to heat for 2 hours to raise the temperature from room temperature to 90° C., maintain this temperature for 48 hours, and then cool down to room temperature after 13 hours.
[0014] In particular, as an optional embodiment, the preparation method of the coordination compound Cd-MOF comprises the following steps: adding a mixture of ligand H2L (0.1mmol, 16.7mg), CdCl2·2.5H2O (0.1mmol, 22.8mg), DMF (1ml), water (1ml) and ethanol (1ml) into a 25ml polytetrafluoroethylene-lined stainless steel container, placing the sealed 25ml polytetrafluoroethylene-lined stainless steel container into an oven, setting the oven program to heat for 2 hours to raise the temperature from room temperature to 90°C, maintaining this temperature for 48 hours, and then cooling down to room temperature after 13 hours. Finally, filtering to obtain colorless block crystals.
[0015] The present invention has the following beneficial effects:
[0016] (1) The present invention provides a metal chain support and heavy atom effect to endow Cd-MOF with adjustable LPL
[0017] (2) The coordination compound Cd-MOF can be used for anti-counterfeiting. The prepared material can accurately and conveniently encrypt and decrypt information by switching ultraviolet irradiation. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 a) IR spectrum, b) simulated and synthesized powder X-ray diffraction and c) thermogravimetric analysis of Cd-MOF.
[0019] Figure 2 Single crystal of H2L. a) Asymmetric unit. bc) 1D chain structure formed by intermolecular hydrogen bonding. d, e) Assembling these 1D chains to form 2D layer structure. f) 3D framework structure.
[0020] Figure 3 Structural features of Cd-MOF. a) Asymmetric unit. b) One-dimensional metal chain. c) Coordination mode of H2L. d) Three-dimensional structure assembled by one-dimensional metal chain and ligand. e) Simplified three-dimensional network.
[0021] Figure 4 Simplified 3D network.
[0022] Figure 5 Solid-state UV-visible spectra of H2L and Cd-MOF.
[0023] Figure 6 Excitation-dependent instantaneous and delayed emission spectra of H2L at room temperature and the corresponding CIE coordinates.
[0024] Figure 7 Excitation-dependent instantaneous and delayed emission spectra of Cd-MOF at room temperature and the corresponding C
[0025] IE coordinates.
[0026] Figure 8 Fluorescence and phosphorescence decay curves of H2L and Cd-MOF at room temperature.
[0027] Fig. 9 a, b) Instantaneous and delayed (1 ms) spectra of H2L and Cd-MOF at room temperature. c) Excitation-dependent delayed (1 ms) spectrum of Cd-MOF at room temperature.
[0028] Fig.10 Excitation spectra of H2L and Cd-MOF at room temperature.
[0029] Fig.11 Photoluminescence quantum efficiency and phosphorescence quantum efficiency of H2L and Cd-MOF at room temperature.
[0030] Fig.12 Prompt and delayed emission spectra of Cd-MOF in air and vacuum at room temperature.
[0031] Fig.13 Decay curves of Cd-MOF in air and vacuum at 515, 540, and 570 nm at room temperature.
[0032] Fig.14 Excitation-dependent gating spectrum of Cd-MOF at 77 K at room temperature. Temperature-dependent emission spectra of Cd-MOF in the range of 300 to 77 K and the corresponding CIE coordinates.
[0033] Fig.15 Temperature-dependent decay curves of Cd-MOF at wavelengths of 515, 540, and 570 nm from 300 to 77 K.
[0034] Fig.16 Temperature-dependent retardation spectra of Cd-MOF under 311, 385, 405, and 450 nm excitations from 300 to 77 K.
[0035] Fig.17 Excitation-dependent instantaneous and delayed emission spectra of Cd-MOF at room temperature and the corresponding CIE coordinates.
[0036] Fig.18LPL of Cd-MOF. a, b) Excitation-dependent LPL spectra at room temperature and 77 K after removing the 275, 311, 365, 385, 405, and 450 nm flashlights (8 ms), respectively. c) Time-resolved LPL spectra after removing the 365 nm flashlight at 100 K. d) Temperature-dependent LPL spectra after removing the 311 nm flashlight. e, f) LPL photos after removing the 450 and 311 nm flashlights from 300-77 K, respectively.
[0037] Fig.19 Photo showing Cd-MOF-based anti-counterfeiting applications.
[0038] Fig. 20 The encrypted pattern of the number "8" was manually made using CdCl2, H2L, and Cd-MOF. Positions ①, ②, and ⑥ were engraved with Cd-MOF, while positions ③, ④, and ⑦ were engraved with H2L. In addition, position ⑤ was marked with CdCl2. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0040] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0041] Example 1 Preparation of complex Cd-MOF
[0042] A mixture of ligand H2L (0.1mmol, 16.7mg), CdCl2·2.5H2O (0.1mmol, 22.8mg), DMF (1ml), water (1ml) and ethanol (1ml) was added to a 25ml polytetrafluoroethylene-lined stainless steel container, and the sealed 25ml polytetrafluoroethylene-lined stainless steel container was placed in an oven, and the oven program was set to heat for 2 hours to raise the temperature from room temperature to 90°C, keep this temperature for 48 hours, and then cool to room temperature after 13 hours. Finally, colorless block crystals were obtained by filtration.
[0043] Example 2 Crystallographic Data
[0044] X-ray diffraction intensity data were obtained at room temperature on a Bruker Apex IICCD diffractometer with graphite monochromated Mo radiation. The structure was solved by direct method and refined by full matrix least squares method using SHELXL-2014 package. All hydrogen atoms were located at the calculated positions and refined anisotropically. Detailed crystallographic data are shown in Table 1.
[0045] Table 1 Crystallographic data
[0046]
[0047]
[0048] Example 3: Structural analysis of Cd-MOF crystals
[0049] H2L crystals were obtained by supersaturating the powdered ligand and crystallizing in ethanol solvent. Cd-MOF was synthesized by hydrothermal reaction of H2L and CdCl2 in a mixture of DMF, EtOH and H2O at 90 °C for 2 days. IR spectra were shown in Figure 2. Figure 1 a. The diffraction peaks of the powder X-ray diffraction of Cd-MOF fully match the simulated data obtained from the single crystal data, proving its high phase purity ( Figure 1 b) The thermal stability was studied by thermogravimetric analysis. Figure 1 c, the structural integrity can be maintained up to about 350°C. Specifically, when the temperature rises from room temperature to 190°C, the coordinated water molecules escape. However, when the temperature exceeds 350°C, H2L liquefies, subsequently initiating framework collapse. Single crystal X-ray analysis shows that H2L crystallizes in the orthorhombic system and belongs to the P212121 space group. The asymmetric unit of H2L contains a ligand with proton transfer, in which the carboxyl proton is transferred to the pyridine nitrogen atom, resulting in the formation of an intramolecular salt ( Figure 2 a). Figure 2 As shown in b and 2c, H2L forms 1D chains through NH hydrogen bonds or OH hydrogen bonds along different directions. These chains are further extended through CH hydrogen bonds to form two-dimensional frameworks ( Figure 2 d and 2e). Ultimately, H2L assembles into a three-dimensional hydrogen-bonded organic framework driven by these non-covalent interactions ( Figure 2 f). For Cd-MOF, it exhibits a 3D network structure and crystallizes in the monoclinic system with a P21 / n space group. The asymmetric unit consists of an L2 - ligand, a coordinating water molecule and a Cd 2+ composition( Figure 3 a) Specifically, Cd1 is hexacoordinated and is bound by four L2 - The four oxygen atoms of the ligand (O1, O2, O3 and O4), a water molecule (O1w) and an L2 - The ligands are surrounded by nitrogen atoms (N1), showing a distorted octahedral geometry. It is noteworthy that these octahedra are connected by μ2-COO carboxyl bridges to form a one-dimensional metal chain ( Figure 3 b). In addition, the ligand adopts a pentadentate (μ5-η 1 :η 1 :η 1:η 1 :η 1 ) coordination mode, connecting these metal chains to each other to produce a three-dimensional framework structure ( Figure 3 c and 3d). The simplified ligands are represented in a five-connected manner, while the metal ions act as connecting nodes, presenting an understandable and simplified network ( Figure 3 e and 4).
[0050] Example 4: Photophysical properties of ligands and complexes
[0051] The solid-state UV-visible spectra of H2L and Cd-MOF show similar absorption shapes in the range of 200-400 nm, with Cd-MOF having a broader absorption ( Figure 5 ). The 200-300nm range can be attributed to the π-π* transition, and the 300-400nm absorption is attributed to the n-π* transition caused by the heteroatoms in H2L. In order to better understand the luminescence properties at room temperature, the photoluminescence spectra were studied. The instantaneous and delayed spectra of H2L and Cd-MOF under various excitations at room temperature are shown in Figure 2. Figure 6 and 7 As shown, similar emission is revealed. The instantaneous spectrum shows that regardless of the excitation wavelength, H2L and Cd-MOF give single emission peaks at 500 and 505nm, respectively. The luminescence lifetime of H2L is 5.75ns and that of Cd-MOF is 5.47ns, thus highlighting the fluorescent properties ( Figure 8 ). However, H2L and Cd-MOF exhibited excitation-dependent delayed emission. Under 360nm excitation, the emission of H2L and Cd-MOF peaked at 535 and 515nm, respectively ( Fig. 9 a and 9b). As the excitation wavelength increases from 310 nm to 430 nm, the delayed emission spectra of H2L and Cd-MOF gradually red-shift ( Figure 6 and 9 c). H2L moves from 520nm to 545nm, while Cd-MOF changes from the initial 515nm to 540nm and then to 570nm. When excited with 440 and 450nm, their delayed spectra both show double peaks near 500 and 570nm. It is worth noting that H2L and Cd-MOF exhibit multiple excited triplets near 500, 540 and 570nm, respectively, which are a combination of single molecules and aggregated states caused by non-covalent interactions. The phosphorescent properties presented by the delayed emission are further supported by time-resolved spectroscopy. The fitted phosphorescence lifetimes of H2L at 500nm, 540nm and 570nm are 42.53ms, 48.19ms and 40.40ms, respectively. Similarly, the lifetimes of Cd-MOF at 515nm, 540nm and 570nm are 124.01ms, 122.14ms and 106.5ms, respectively. Figure 8). After assembly into MOFs, the phosphorescence lifetime increased by 3 times, implying a strong stabilizing effect of the framework. The excitation spectra of fluorescence and phosphorescence of H2L and Cd-MOF were recorded, which consistently showed matching excitation wavelengths at 360-370 nm, revealing that the photoemission of H2L and Cd-MOF came from the same source ( Fig.10 ). Under 360nm excitation, the photoluminescence quantum yield and phosphorescence quantum yield of H2L are 4.20% and 0.79%, respectively, and those of Cd-MOF are 4.95% and 1.04%, respectively. Fig.11 ). Both the phosphorescence lifetime and quantum yield of Cd-MOF are enhanced, reflecting the role of coordination in improving the phosphorescence performance.
[0052] Considering the sensitivity of triplet excitons to the surrounding environment, which could potentially affect the phosphorescent properties, the photoluminescence of Cd-MOF was studied under vacuum and ambient conditions, e.g. Fig.12 When placed in a vacuum environment, the emission intensities of both the immediate and delayed spectra increase while maintaining the spectral shape. More importantly, their phosphorescence lifetimes are prolonged, indicating that molecular oxygen affects and destroys triplet excitons ( Fig.13 ). It is well known that temperature affects phosphorescence. Therefore, temperature-dependent photoluminescence measurements were performed between 300 and 77 K. As the temperature decreases, the transient emission intensity under 370 nm excitation increases and the emission peak slightly red-shifts, as shown in Figure 2. Fig.14 The decay curves monitored at 515, 540 and 570 nm emissions show similar changes. Fig.15 As shown in Figure 2, the phosphorescence lifetime gradually increases with decreasing temperature. This phenomenon is attributed to the suppression of triplet exciton non-radiative transitions at low temperatures. Since Cd-MOF has phosphorescence emission that depends on the excitation wavelength, the phosphorescence spectra were similarly collected at representative excitation wavelengths at low temperatures ( Fig.16 ). Under excitation at 311 and 405 nm wavelengths, the phosphorescence emission is mainly located at 515 and 540 nm, respectively, and is slightly blue-shifted around these wavelengths at low temperatures, which is due to the energy level splitting at low temperatures. Under excitation at 450 nm, the multi-peak emission gradually red-shifts and merges into a single peak at 580 nm. At 77 K, when the excitation wavelength increases from 300 to 450 nm, the gradual red-shift of the phosphorescence emission from blue to yellow is clearly visible. At various excitation wavelengths at 77 K, the CIE coordinates corresponding to the instantaneous and delayed emission spectra are shown in Figure 2. Fig.17 shown.
[0053] Due to the ultra-long phosphorescence lifetime, Cd-MOF exhibits bright LPL emission after the excitation source is removed. According to the presence of multiple phosphorescence emissions, five representative wavelengths of 275, 311, 365, 385, and 405 nm were selected as excitation sources. With the increase of excitation wavelength, the LPL emission moves from 520 to 542 nm at room temperature and then to 575 nm ( Fig.18 a). At 77K, as the excitation wavelength increases, the LPL emission red-shifts from 450nm to 600nm ( Fig.18 b). Interestingly, after turning off the 365 nm radiation source, the time-evolving LPL appears from green to cyan, as shown in the photograph and spectrum ( Fig.18 c), which is caused by the inconsistent multiple triplet decay rates and phosphorescence lifetimes. Fascinatingly, upon removal of the 311 nm excitation from 300 to 77 K, the LPL emission shifts from 540 nm to 470 nm ( Fig.18 d). As the temperature decreases, the LPL color changes from green to blue. The corresponding LPL picture is as follows: Fig.18 f. At low temperatures, removing the 450nm excitation wavelength can gradually capture the yellow LPL ( Fig.18 e). Therefore, Cd-MOF exhibits fascinating multicolor LPL due to the existence of multiple triplet states.
[0054] Example 5 Application of coordination compound Cd-MOF
[0055] Multi-color anti-counterfeiting work example
[0056] The excellent and adjustable LPL performance of Cd-MOF endows this material with applications in display, anti-counterfeiting and advanced encryption technologies. Fig.19 As shown, the snowflake material is made of Cd-MOF used in display technology. It appears white in sunlight and emits blue fluorescence when exposed to 365nm UV irradiation. After removing the UV light source, the snowflake exhibits a green LPL lasting 1 second. Considering that CdCl2, H2L and Cd-MOF have different luminescence lifetimes and exhibit different LPL durations, time-resolved information security is further developed. In addition, the three materials are applied to manually manufacture an encrypted pattern of the number "8" on a piece of non-fluorescent paper. Positions ①, ②, and ⑥ are engraved with Cd-MOF, and positions ③, ④, and ⑦ are engraved with H2L ( Fig. 20). In addition, position ⑤ is marked with CdCl2. In the same way, the numbers written using different materials show white patterns under daylight and blue emission under 365nm UV irradiation light. It is worth noting that the number immediately exhibits bright green LPL after the exposure is turned off. However, due to the difference in LPL lifetimes between CdCl2, H2L and Cd-MOF, the number "9" becomes visible within 1 second, while only the number "7" can be discerned after more than 3 seconds. Therefore, ingenious and multifaceted anti-counterfeiting / encryption technologies can be achieved through the fusion of these materials.
[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. For ordinary technicians in this field, other different forms of changes or modifications can be made based on the above descriptions and ideas. It is not necessary and impossible to list all the implementation methods here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. An organic ligand based on a metal chain scaffold and a heavy atom effect-assisted metal, characterized in that: Its molecular formula is C7H5CdNO5, it belongs to the monoclinic system, and its space group is P 21 / n.
2. The method for preparing an organic ligand based on a metal chain scaffold and a heavy atom effect-assisted metal according to claim 1, characterized in that: The coordination compound Cd-MOF is prepared by using ligand 3,4-pyridinedicarboxylic acid (H2L) and CdCl2·2.5H2O as raw materials, comprising the following steps: S1. Mix the ligand H2L and CdCl2·2.5H2O in a molar ratio of 1:1~2 and put them into a 25 ml polytetrafluoroethylene-lined stainless steel container. Add DMF, water and ethanol in a volume ratio of 1:1:1~1:2:2 into the 25 ml polytetrafluoroethylene-lined stainless steel container and shake gently to mix evenly: the usage ratio of DMF and ligand H2L is 1 ml: 0.01~0.02mmol; S2. Place a sealed 25 ml PTFE-lined stainless steel container in an oven and set the program to heat for 1 to 2 hours, raising the temperature from room temperature to 90 to 110 o C, keep this temperature for 40 to 60 hours, and then cool down after 8 to 13 hours; S3. Collect colorless block crystals by filtration.
3. The method for preparing an organic ligand based on a metal chain scaffold and a heavy atom effect-assisted metal according to claim 2, characterized in that: In step S1, the molar ratio of the ligand H2L and CdCl2·2.5H2O is 1:
1.
4. The method for preparing an organic ligand based on a metal chain scaffold and a heavy atom effect-assisted metal according to claim 2, characterized in that: The volume ratio of DMF, water and ethanol in step S1 is 1 ml: 1 ml: 1 ml.
5. The method for preparing an organic ligand based on a metal chain scaffold and a heavy atom effect-assisted metal according to claim 2, characterized in that: The usage ratio of DMF to ligand H2L in step S1 is 1 ml: 0.1 mmol.
6. The method for preparing an organic ligand based on a metal chain scaffold and a heavy atom effect-assisted metal according to claim 2, characterized in that: Step S2: The oven program is set to heat for 2 hours so that the temperature rises from room temperature to 90 o C, keep this temperature for 48 hours, and then cool down to room temperature after 13 hours.
7. The method for preparing an organic ligand based on a metal chain scaffold and a heavy atom effect-assisted metal according to claim 2, characterized in that: The method comprises the following steps: adding a mixture of ligand H2L (0.1 mmol, 16.7 mg), CdCl2·2.5H2O (0.1 mmol, 22.8 mg), DMF (1 ml), water (1 ml) and ethanol (1 ml) into a 25 ml polytetrafluoroethylene-lined stainless steel container, placing the sealed 25 ml polytetrafluoroethylene-lined stainless steel container into an oven, and setting the oven program to heat from room temperature to 90 °C for 2 hours. o C, keep this temperature for 48 hours, then cool to room temperature after 13 hours, and finally filter to obtain colorless block crystals.
Citation Information
Patent Citations
Production method of dipicolinic acid chelating cadmium selenide and terbium quantum dots
CN104861979A
Metal halide-based metal-organic framework (MOFs) materials with multicolor tunable long persistent luminescence and white light properties
CN116606443A